Effect of surface modification and H2 reduction of WO3 nanoparticles in Methylene Blue photodegradation. (21st October 2020) - Siddique, Fizza; Gonzalez-Cortes, Sergio; Xiao, Tiancun; Rafiq, M A; Edwards, Peter P
Abstract: We report the chemical synthesis of WO3 nanoparticles, PtOx –WO3 nanoparticles and Pt–WO3 nanoparticles with an average particle size of 20 nm. X-ray diffraction confirmed the formation of crystalline nanoparticles and the transmission electron microscope (TEM) images clearly show the presence of elemental Pt on WO3 nanoparticles (NPs). Moreover, Energy Dispersive x-ray spectroscopy (EDX) and Raman spectroscopy confirm the presence of Pt on the surface of WO3 NPs. The bandgap of WO3, PtOx –WO3 and Pt–WO3 was 2.78 eV, 2.59 eV and 2.28 eV respectively as determined by UV visible (UV–vis) spectroscopy. The H2 -Temperature Programme Reduction (TPR) of WO3 and PtOx –WO3 NPs confirms the increase in interaction of H2 with PtOx –WO3 NPs. The photocatalytic performance of WO3 NPs, PtOx –WO3 NPs and Pt–WO3 NPs was investigated for Methylene Blue (MB) degradation. Samples of PtOx –WO3 showed higher photocatalytic rate for MB degradation than WO3 NPs. Importantly, a further increase in MB degradation efficiency was observed using Pt–WO3 NPs photocatalyst. Apparent reaction rate constants ' kapp ' for MB degradation, calculated from a Langmuir model are 0.003 ± 0.001 min −1, 0.018 ± 0.003 min −1 and 0.040 ± 0.001 min −1 for WO3, PtOx –WO3 and Pt–WO3 NPs photocatalyst respectively. The increase in the degradation performance was attributed to surface defects and surface generation of oxygen vacancies during H2 reduction. The Pt–WO3 NPs exhibited 94.7 ± 0.6% Safranin-O (SO) degradation in 80 min and in this case the k a p p 0.027 ± 0.001 min −1 .